Computer ethics - Brinkman, William 'Bo' John, II.; Sanders, Alton 'Al' F. (Singapore : Cengage Learning Asia Pte Ltd, 2012)
COMPUTER ETHICS introduces key ideas in moral theory and professionalism to explore the hottest topics in computer ethics. With a unique blend of theory, application, and critical thinking exercises, each chapter underscores the interdisciplinary links between computing and diverse areas of study. Abundant multicultural cases are presented throughout to highlight contrasts and conflicts in ethical perspectives across the globe. COMPUTER ETHICS encourages students to continually read, reflect and write to hone sharp critical thinking skills. Students learn that that computing is not a purely technical discipline but one with moral and social implications that affect everyday life.
Critical reasoning and moral theory -- Computing professions and professional ethics -- Privacy -- Intellectual nd intangible property -- Trust, safety, and reliability -- How computing is changing who we are -- Democracy, freedom of speech, and freedom of the press -- Computing and vulnerable groups -- Autonomous and pervasice technology.
Other title: "Ethics in a computing culture"
Includes bibliographical references and index.
Keywords: ELECTRONIC DATA PROCESSING -- MORAL AND ETHICAL ASPECTS